The Militar Gränitz Rechten: An 18th Century Legal Reform of Military Frontier (Povijesni prilozi (Historical Contributions), 2019)
This article analyses one of the most important legal documents in the history of theMilitary Frontier in the 18th century, primarily from the social and legal point of view.The document in question was a medium of centralisation and legal modernisationcarried out at the time by the court in Vienna.